2020
DOI: 10.1073/pnas.2006828117
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid biosynthesis pathway determines ferroptosis sensitivity in gastric cancer

Abstract: Ferroptosis is an iron-dependent regulated necrosis mediated by lipid peroxidation. Cancer cells survive under metabolic stress conditions by altering lipid metabolism, which may alter their sensitivity to ferroptosis. However, the association between lipid metabolism and ferroptosis is not completely understood. In this study, we found that the expression of elongation of very long-chain fatty acid protein 5 (ELOVL5) and fatty acid desaturase 1 (FADS1) is up-regulated in mesenchymal-type gastric cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
197
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 305 publications
(242 citation statements)
references
References 48 publications
8
197
1
Order By: Relevance
“…Transcriptome analysis suggested that there were no significant changes in the levels of fatty acid transporters during this process. Interestingly, we found that FATP2 levels are relatively low in mesenchymal-type GC cells, implying that fatty acid import is somewhat limited in these cells; therefore, these cells are dependent on PUFA biosynthesis [63]. Although AA is regarded as a primary target for lipid peroxidation, ELOVL5-depleted GC cells still contain comparable amounts of AA and PE-AA, possibly activating AA import [63].…”
Section: Pufa Biosynthesis Pathway and Ferroptosismentioning
confidence: 85%
See 4 more Smart Citations
“…Transcriptome analysis suggested that there were no significant changes in the levels of fatty acid transporters during this process. Interestingly, we found that FATP2 levels are relatively low in mesenchymal-type GC cells, implying that fatty acid import is somewhat limited in these cells; therefore, these cells are dependent on PUFA biosynthesis [63]. Although AA is regarded as a primary target for lipid peroxidation, ELOVL5-depleted GC cells still contain comparable amounts of AA and PE-AA, possibly activating AA import [63].…”
Section: Pufa Biosynthesis Pathway and Ferroptosismentioning
confidence: 85%
“…AA and AdA are ω-6 fatty acids and can be synthesized from linoleic acid (LA) through the ω-6 de novo PUFA synthesis pathway using ELOVL2, ELOVL5, FADS1 and FADS2 (Figure 2a). These enzymes seem to play an essential role in ferroptosis [63,64]. In particular, intestinal-type gastric cancer (GC) cells express extremely low levels of ELOVL5 and FADS1 due to hypermethylation at the promoter region and are resistant to ferroptosis, while mesenchymal-type GC cells are sensitive to ferroptosis at high levels of ELOVL5 and FADS1 [63].…”
Section: Pufa Biosynthesis Pathway and Ferroptosismentioning
confidence: 99%
See 3 more Smart Citations